The complexity of pure equilibria in mix-weighted congestion games on parallel links - Monien, Burkhard; Mavronicolas, Marios (Information Processing Letters)
We revisit the simple class of weighted congestion games on parallel links [10], where each player has a non-negative weight and her cost on the link she chooses is the sum of the weights of all players choosing the link. We extend this class to mix-weighted congestion games on parallel links, where weights may as well be negative. For the resulting simple class, we study the complexity of deciding the existence of a pure equilibrium, where no player could unilaterally improve her cost by switching to another link.We show that even for a singlenegative weight, this decision problem is strongly NP-complete when the number of links is part of the input; the problem is NP-complete already for two links. When the number of links is a fixed constant, we show, through a pseudopolynomial, dynamic programming algorithm, that the problem is not strongly NP-complete unless P = NP; the algorithm works for any number of negative weights.

Systematically Deriving Quality Metrics for Cloud Computing Systems - Becker, Matthias; Lehrig, Sebastian; Becker, Steffen (Proceedings of the 6th ACM/SPEC International Conference on Performance Engineering)
In cloud computing, software architects develop systems for virtually unlimited resources that cloud providers account on a pay-per-use basis. Elasticity management systems provision these resources autonomously to deal with changing workload. Such changing workloads call for new objective metrics allowing architects to quantify quality properties like scalability, elasticity, and efficiency, e.g., for requirements/SLO engineering and software design analysis. In literature, initial metrics for these properties have been proposed. However, current metrics lack a systematic derivation and assume knowledge of implementation details like resource handling. Therefore, these metrics are inapplicable where such knowledge is unavailable.To cope with these lacks, this short paper derives metrics for scalability, elasticity, and efficiency properties of cloud computing systems using the goal question metric (GQM) method. Our derivation uses a running example that outlines characteristics of cloud computing systems. Eventually, this example allows us to set up a systematic GQM plan and to derive an initial set of six new metrics. We particularly show that our GQM plan allows to classify existing metrics.

Bonding of Wood Plastic Composites (WPC) - Material and Surface Modification for Special Applications - Moritzer, Elmar; Hopp, Matthias (68th Annual Assembly of the International Institute of Welding (IIW))

Kleben von Wood-Plastic-Composites (WPC) - Material- und Oberflächenmodifizierung für spezielle Anwendungen - Moritzer, Elmar; Hopp, Matthias (Jahresmagazin Kunststofftechnik)

Systematic Development and Re-Use of Model Tranformations - Besova, Galina

SynRace: Decentralized Load-Adaptive Multi-path Routing without Collecting Statistics - Schwabe, Arne; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
Multi-rooted trees are becoming the norm for modern data-center networks. In these networks, scalable flow routing is challenging owing to vast number of flows. Current approaches either employ a central controller that can have scalability issues or a scalable decentralized algorithm only considering local information. In this paper we present a new decentralized approach to least-congested path routing in software-defined data center networks that has neither of these issues: By duplicating the initial (or SYN) packet of a flow and estimating the data rate of multiple flows in parallel, we exploit TCP’s habit to fill buffers to find the least congested path. We show that our algorithm significantly improves flow completion time without the need for a central controller or specialized hardware.

Reputation und Vertrauen auf Online-Märkten - Sonntag, Melissa

Rating Aggregation in Multi-Dimensional Rating Systems: How Do Reviewers Form Overall Ratings? - Gutt, Dominik; Kundisch, Dennis (INFORMS Annual Meeting)

Quantitative Evaluation of Model-Driven Performance Analysis and Simulation of Component-based Architectures - Brosig, Fabian; Meier, Philipp; Becker, Steffen; Koziolek, Anne; Koziolek, Heiko; Kounev, Samuel (Transactions on Software Engineering)
During the last decade, researchers have proposed a number of model transformations enabling performance predictions. These transformations map performance-annotated software architecture models into stochastic models solved by analytical means or by simulation. However, so far, a detailed quantitative evaluation of the accuracy and efﬁciency of different transformations is missing, making it hard to select an adequate transformation for a given context. This paper provides an in-depth comparison and quantitative evaluation of representative model transformations to, e.g., Queueing Petri Nets and Layered Queueing Networks. The semantic gaps between typical source model abstractions and the different analysis techniques are revealed. The accuracy and efﬁciency of each transformation are evaluated by considering four case studies representing systems of different size and complexity. The presented results and insights gained from the evaluation help software architects and performance engineers to select the appropriate transformation for a given context, thus signiﬁcantly improving the usability of model transformations for performance prediction.

Protokolle zur authentifizierten Schüsselvereinbarung - Eisenhofer, Thorsten

Evaluation of the Efficiency of Filtration Processes Using Precoat Materials - Schiller, Sascha; Hellmich, Christoph; Schmid, Hans-Joachim (Chemical Engineering & Technology)
The highly efficient filtration of ultrafine dust emitted by biomass combustion processes with a baghouse filter has been successfully tested in the last years. To protect the filter material from the very small and sticky fine dust particles and to guarantee very high total collection efficiencies (> 99 %) in a long-term stable process, the use of a precoat is necessary. Tests done in a laboratory and a real-application plant show that the reuse of precoat materials can lead to significant savings. Considering the influences of different combustion processes, the associated precoat efficiencies could be calculated. With these characteristic ratios, it is possible to evaluate different process settings. Hence, the amount and the cost of the needed precoat could be reduced significantly.

Process Development of a Liquid-Liquid Phase Transfer of Colloidal Particles for Production of High-Quality Organosols - Erler, Jacqueline V.; Machunsky, Stefanie; Franke, Steffen; Grimm, Philipp; Schmid, Hans-Joachim; Peuker, Urs A. (Colloid Process Engineering)
The emphasis of the study presented is on a new process of particle extraction to transfer magnetite nanoparticles from an aqueous into an immiscible organic phase directly through the liquid-liquid interface. For the production of high-quality organosols, stabilized colloidal and functionalized particles are required in a liquid organic phase. The mechanism of phase transfer is initiated by adsorption and chemical binding of surfactants (fatty acids) at the particle surface. The resulting physico-chemical dispersion of the hydrophobically modified particles leads to the formation of the stabilized organic colloid, or organosol. The aim here is to demonstrate the entire chain of the transfer process in a continuous miniplant, which comprises particle synthesis, conditioning, and transfer, and which uses a drop column for extraction and as a transfer device. Based on the investigation of the governing principles and the material parameters, the results obtained for the transfer kinetics in the individual contact devices (centrifuge, single-drop column, and drop column for different operations) are used for the dimensioning of the entire process chain.

Bipolar charge distribution of a soft X-ray diffusion charger - Tigges, L.; Wiedensohler, A.; Weinhold, K.; Gandhi, J.; Schmid, Hans-Joachim (Journal of Aerosol Science)
The conditioning of the aerosol particle population into a bipolar charge equilibrium is an essential prerequisite to calculate the particle number size distribution using mobility particle size spectrometers. This is commonly realized by diffusion charging of bipolar air ions generated by e.g. a 85Kr source. Because of strict legal regulations on radioactive sources in several countries, soft-X-ray (SXR) appears as a suitable alternative. However, multiple measurements showed a systematical and significant difference between the particle charge distribution delivered by a radioactive source and an SXR charger, respectively. In this investigation, a calibrated particle charge distribution, suitable for the SXR chargers, was calculated based on the Fuchs model. An approximation analogous to the commonly used Wiedensohler approximation formula (Wiedensohler, 1988) was computed. The use of the new SXR approximation of the bipolar charge equilibrium for the inversion of an electrical mobility distribution to a particle number size distribution improves the comparability of these results, compared to measurements involving a 85Kr charger or to bipolar chargers using radioactive material in general. A systematic error in case of using the SXR charger could be eliminated and hence the root mean square deviation could be reduced from 13% using the common parameters for both charger types to 7% using the new SXR approximation for the SXR bipolar charger.

On the bipolar charge distribution used for mobility particle sizing: Theoretical considerations - Tigges, L.; Jain, A.; Schmid, Hans-Joachim (Journal of Aerosol Science)
An essential part of mobility particle size spectroscopy is the prediction of the aerosol charge distribution in a highly concentrated bipolar ion environment. This charge distribution can be readily calculated, but is depending on several environmental conditions. These influences are investigated theoretically. The first part of this work deals with a sensitivity analysis using the Fuchs model (Fuchs, 1963) to determine the variation of the resulting charge distributions depending on the input parameters. It is demonstrated, that the main influencing variable is the difference between the positive and negative ion mobility. A sensitivity analysis reveals that a reasonable variation of the ion mobilities may lead to variations of the particle density distribution up to±20%. The second part investigates the evolution of the charge distribution along the tubing downstream of the bipolar charger exit starting with equal ion concentrations for positive and negative ions. Due to wall losses depending on ion mobility a non-equilibrium charge distribution is developing along the plumbing. The evolution of the particle charge distribution is determined using a coupled population balance model. Even though the non-equilibrium character is clearly shown, it turns out that this effect is negligible at conditions typical for particle size measurements.

Highly efficient filtration of ultrafine dust in baghouse filters using precoat materials - Schiller, Sascha; Schmid, Hans-Joachim (Powder Technology)
The precipitation of sticky and ultrafine particles has become increasingly important. Biomass burners are one important example for ultrafine dust emission sources with ever growing importance. Therefore, a baghouse filter has been developed, which combines excellent separation efficiency (> 99%, clean air dust loading of < 1 mg/m3) with convenience in operation. However, in order to prevent clogging of the filter cloth by sticky and ultrafine particles, it is necessary to use a precoat layer (e.g. hydrated limestone powder). If this technology is applied to larger scale processes, e.g. biomass burning for industrial drying processes, the reuse of the precoat material can generate significant savings. Therefore, extended tests on recycling of used precoat material have been performed. Particularly, the influence of precoat injection parameters and various mixing strategies of used and virgin powder for refreshing the precoat material have been investigated. Different mixtures have been characterised by their ability to disintegrate, flowability and filtration behaviour. It is clearly demonstrated that upon redispersing the used precoat fine dust mainly adheres to the coarse precoat with only a limited number of dust agglomerates being produced in addition. For each kind of precoat a minimum amount is determined in order to ensure a long-term stable process. This way a saving potential of between 40–67% has been found. An economic and ecologic process has been developed to precipitate ultrafine dust in a baghouse filter system using precoat materials.

Simulation of Capillary Bridges between Particles - Dörmann, Michael; Schmid, Hans-Joachim (Procedia Engineering)
Capillary forces between particles often dominate other adhesion forces. However, the calculation of the shape of capillary bridges and the resulting force is complex, so often assumptions and approximations are used. These assumptions are not useful for nanoscale particles. Therefore, a simulation method was established to calculate numerically the shape of the meniscus and derive the corresponding capillary bridge force. The main focus are nanoscaled particles with liquid bridges formed by condensing air humidity. The dependence of the capillary force on various parameters such as particle sizes, contact angle and humidity was investigated and it is demonstrated that often-used assumptions cannot be used for nanoscaled particles without remarkable mistake.

Unscharfe Produktionsmengenplanung als Instrument des Risikomanagements in Supply Chains - Betz, Stefan (Risikomanagement in Supply Chains)

Bedarfsorientiertes Kapazitätsmanagement in Supply Chains - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Internationale Standortwahl als strategisches Logistikproblem - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Dual-path source engineering in integrated quantum optics - Kruse, Regina; Sansoni, Linda; Brauner, Sebastian; Ricken, Raimund; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review A)